The Structure and Nephroprotective Activity of Oligo-Porphyran on Glycerol-Induced Acute Renal Failure in Rats - Jing Wang; Yun Hou; Delin Duan; Quanbin Zhang (Marine Drugs, 2017)
Porphyran is a sulfate galactan in the cell wall of Porphyra. Its acid hydrolysis product, oligo-porphyran (OP), was prepared and the structure studied by electrospray ionization time-of-flight mass spectrometry (ESI-TOF-MS). This oligosaccharide was mainly composed of monosulfate-oligo-galactan, disufate-oligo-galactan, trisulfate-oligo-galactan, trisulfate oligo-methyl-galactan, and 3,6-anhydrogalactose with the degree of polymerization ranging from 1 to 8. The effects of OP were investigated in the glycerol-induced acute renal failure (ARF) model. Compared with the normal group, rats from the glycerol-induced group exhibited collecting duct and medullary ascending limb dilation and casts. The OP-treated group exerted a protective effect against glycerol-induced changes. The results showed that the administration of OP markedly decreased mortality in female ARF rats. For male ARF rats, all of which survived, OP significantly decreased the blood urea nitrogen and serum creatinine levels. Ion levels in plasma and urine were significantly changed in ARF rats, whereas OP treatment almost recovered ion levels back to normal. This study showed a noticeable renal morphologic and functional protection by OP in glycerol-induced ARF rats.